EXTRACTS OF EDIBLE PODS OF MORINGA OLEIFERA LAM. (MORINGACEAE) AS NOVEL ANTIBACTERIAL AGENT AGAINST SOME PATHOGENIC BACTERIA - DEVALEENA MUKHERJEE; KUNTAL BHATTACHARYA; GOUTAM CHANDRA (International Journal of Pharma and Bio Sciences, 2015)
Moringa oleifera (Lam.) is well known for wide range of medicinal activities and contribution to dietary diversity. The present study focused on investigating the antibacterial potentiality of the crude extract and different solvent extracts of the pods of M. oleifera using agar well diffusion method against pathogenic gram negative bacterial strains namely Pseudomonas fluorescens and Pseudomonas putida and gram positive bacterial strains namely Bacillus mycoides and Bacillus licheniformis. The best result was showed by Petroleum ether extract against the said bacteria. M.I.C. of the aforementioned extract on gram negative bacteria P. fluorescens and P. putida were found to be 28.6 μg/ml and 32.0 μg/ml respectively while 39 μg/ml and 42 µg/ml values were obtained for gram positive bacteria B. mycoides and B. licheniformis respectively. The petroleum ether extract of M. oleifera pods may act as a novel and effective antibacterial agent.